2020
DOI: 10.3906/biy-2002-30
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anticarcinogenic properties of Viburnum opulus and its active compound p-coumaric acid on human colorectal carcinoma

Abstract: Resistance to therapeutic agents and the highly toxic side effects of synthetic drugs has spurred new research in the treatment of colon cancer, which has high morbidity and mortality ratios. This study aims to clarify the molecular mechanisms of the anticarcinogenic properties of methanol extract of Viburnum opulus L. (EVO)and its main active compound, trans-p -coumaric acid ( p -CA), on human colon cancer cells (DLD-1, HT-29, SW-620, Caco-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Asiatic acid, caffeic acid, p-coumaric acid, kaempferol, quercetin, rutin, and ursolic acid were isolated compounds with previously profound antiproliferative action to this cell line. In the study by Karakurt et al (2020), p-coumaric acid exhibited selective inhibition of Caco-2 and HT-29 cells compared to that of healthy colon epithelial cells (CCD-18Co). Since the decoction from the leaves of M. malabathricum L. is also traditionally consumed to treat diarrhea, we suggest a similar composition of bioactive compounds to be present in M. saigonense (Kuntze) Merr.…”
Section: Discussionmentioning
confidence: 97%
“…Asiatic acid, caffeic acid, p-coumaric acid, kaempferol, quercetin, rutin, and ursolic acid were isolated compounds with previously profound antiproliferative action to this cell line. In the study by Karakurt et al (2020), p-coumaric acid exhibited selective inhibition of Caco-2 and HT-29 cells compared to that of healthy colon epithelial cells (CCD-18Co). Since the decoction from the leaves of M. malabathricum L. is also traditionally consumed to treat diarrhea, we suggest a similar composition of bioactive compounds to be present in M. saigonense (Kuntze) Merr.…”
Section: Discussionmentioning
confidence: 97%
“…SW620 and HT-29 cells were seeded into a 24-well plate and treated with 7.2 µmol L -1 and 37.6 µmol L -1 of TA, respectively for 48 h at 37 °C and 5 % CO 2 . The cells were harvested, counted with TC20 automated cell counter, and 5 × 10 3 of cells were transferred into a 6-well plate containing 1 % base agar as described in our previous study and incubated at 37 °C and 5 % CO 2 for 15 days (32). The colonies were then stained with 0.1 % toluidine blue and the number of colonies was counted and analyzed by Image J software.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“… 5 Indeed, a growing body of evidence shows that western dietary pattern, with a predominance of high red meat and alcohol consumption at the expense of vegetable intake, is prospectively associated with CRC risk. 10 , 11 On the other hand, it has been suggested that adherence to the Mediterranean diet (MedDiet) is associated with a lower risk for cancers, including CRC. 12 Polyphenols are the most prevalent antioxidants among MedDiet nutraceuticals and have a wide variety of pharmacological actions such as anti-inflammatory and antitumorigenic properties.…”
Section: Introductionmentioning
confidence: 99%